AsykÄl at-Taá¸¥awwul al-lughawi fÄ« al-Muá¸¥Ädaá¹¡ah al-â€˜Arabiyyah ladÄ ThullÄb Maâ€™had YanbÅ«â€™ al-Qur`Än - Sholihah, Niswatush; Mayasari, Noor Shofiana (LISANIA: Journal of Arabic Education and Literature, 2020)
This was a qualitative research with listening and conversation as data collection techniques. The results described the students’ conversation process by using Arabic and English in boarding environment. The application is using Arabic in the first and second week, and English in the third and fourth week. The forms of code mixing in muhadatsah at Pondok Tahfidz Yanbu’ul Qur’an Menawan included inner and outer code mixing. Inner code mixing happened in the form of words, sentences and abbreviations. Outer code mixing occured in the form of words and sentences. Factors causing code mixing at the PTYQM Kudus included linguistic and non-linguistic factors. Linguistic factors were such as bilingualism, speech partners and vocabulary limitations. Non-linguistic factors were such as Arabic habits carried in Indonesian, fear of regulation, fear of being sanctioned, and increasing a sense of humor. The efforts to overcome the occurrence of code mixing at PTYQM were by giving attention and emphasis in training students, writing the correct form of code mixing on the board often visited by students, fostering students' awareness of the importance of Arabic for the future.